Genomic regulation of plant mating systems: flexibility and adaptative potential. A commentary on: ‘A new genetic locus for self-compatibility in the outcrossing grass species perennial ryegrass (Lolium perenne)’ - Mable, Barbara K (Ann Bot, 2021)
This article comments on: Lucy M. Slatter, Susanne Barth, Chloe Manzanares, Janaki Velmurugan, Iain Place and Daniel Thorogood A new genetic locus for self-compatibility in the outcrossing grass species perennial ryegrass (Lolium perenne), Annals of Botany, Volume 127, Issue 6, 7 May 2021, Pages 715–722, https://doi.org/10.1093/aob/mcaa140